Plasma pTau181 dan Gejala Neuropsikiatri pada Demensia Alzheimer: Sebuah Studi Cross-Sectional - Fadhilah, Nailatul; Syafrita, Yuliarni; Susanti, Restu; Indra, Syarif; Susanti, Lydia; Putri, Fanny Adhy (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Alzheimer’s disease is the leading cause of dementia, marked by progressive cognitive decline and neuropsychiatric disturbances collectively known as behavioral and psychological symptoms of dementia (BPSD). Plasma phosphorylated tau at threonine-181 (pTau181) has emerged as a minimally invasive biomarker of tau-related neurodegeneration, but its association with BPSD remains uncertain. This study investigated the relationship between plasma pTau181 levels and BPSD in Alzheimer’s dementia. An analytical observational study with a cross-sectional design was conducted in patients clinically diagnosed with predefined eligibility criteria. Plasma pTau181 concentrations were measured using enzyme-linked immunosorbent assay (ELISA), while BPSD was assessed using the Neuropsychiatric Inventory Questionnaire (NPI-Q). Statistical analyses were performed to examine associations between plasma pTau181 and BPSD status. Plasma pTau181 levels ranged from 4.32 to 97.23 pg/mL, with a median plasma pTau181 level of 19.29 pg/mL (IQR: 11.81-25.05) in patients without BPSD and 20.67 pg/mL (IQR: 11.81-43.41) in those with BPSD. No significant differences in pTau181 levels were observed between patients with and without BPSD (p = 0.310). These findings suggest that plasma pTau181 may not be directly related to the presence of BPSD in Alzheimer’s dementia. While plasma pTau181 remains a promising biomarker of tau pathology, its predictive value for neuropsychiatric symptoms appears limited. Longitudinal studies are needed to explore its role in BPSD pathophysiology further.